Desarrollo de una pasta a partir de las harinas precocidas de chocho (Lupinus mutabilis) y trigo (Triticum aestivum) para la elaboracion de una sopa instantánea - Cando Chata, Jessenia Nataly (2025)
The objective of this research was to develop a pasta using precooked flours from chocho (Lupinus mutabilis) and wheat (Triticum aestivum) for the preparation of an instant soup. A literature review was conducted on the raw materials, the pasta production process, and lyophilization as a technique to extend the product’s shelf life. An A × B (3×2) experimental design was applied, where Factor A corresponded to the percentage of flours, and Factor B to the precooking temperature. Protein, moisture, fat, acidity, and ash content were analyzed in the raw materials, while the final product was evaluated through sensory, microbiological, and protein analyses. The results showed that wheat flour had the highest moisture content (12.82%), whereas chocho flour had higher levels of ash (2.37%), fat (22.22%), and protein (54.53%). ANOVA revealed that Treatment 4 (15% chocho, 77% wheat, 8% condiments, precooked at 70 °C) achieved the highest protein content (21.69%). The precooking time for all treatments was five minutes. In the sensory analysis, treatments T2, T3, and T4 were rated highest in terms of color, aroma, flavor, and texture, with T4 being the most preferred. Conversely, T6 received the lowest acceptance. Microbiological analysis confirmed the absence of E. coli, molds, yeasts, and Salmonella, demonstrating the product’s safety. It is concluded that both the proportion of flours and the precooking temperature significantly influence the protein content, with chocho proving to be a viable ingredient for enriching pasta-type products.